2017
DOI: 10.2147/rrfms.s125782
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent loss of mRNA transcripts from forensic stains

Abstract: Forensic applications of RNA analysis have included body fluid identification and analysis of RNA degradation in aged stains as a possible indicator of time. With respect to age estimation of a stain through RNA analysis, a full understanding of the patterns and rates of RNA degradation in postmortem samples and body fluid stains is lacking. In this study, mRNA degradation in fresh and aged body fluid stains (blood, saliva, semen, and vaginal fluid) was analyzed utilizing next-generation RNA sequencing (RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 18 publications
1
36
3
Order By: Relevance
“…Weinbrecht et al sequenced the transcriptome of blood, saliva, semen, and vaginal secretion samples, aged up to 1 year [37]. The degradation patterns of the transcripts in each samples type was monitored to better understand the aging of forensically relevant body fluids.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Weinbrecht et al sequenced the transcriptome of blood, saliva, semen, and vaginal secretion samples, aged up to 1 year [37]. The degradation patterns of the transcripts in each samples type was monitored to better understand the aging of forensically relevant body fluids.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…3). The unpaired Wilcoxon non-parametric test did find a significant difference between donor concentrations from 13 bloodstains deposited for hours or less (W = 724, p-value <0.001). No significant difference was found between donor concentrations for bloodstains aged for more than hours (W = 240, p-value = 0.2888).…”
Section: Total Rna Concentrationmentioning
confidence: 91%
“…Using rhythmic biomarkers, which are mRNAs that vary according to the time of day, alongside melatonin and cortisol levels, Lech et al [12] were able to classify bloodstains as having been deposited across three time of day periods with high prediction accuracy. Recent high throughput sequencing (HTS) research by Weinbrecht et al [13] demonstrated that the abundance of mRNA transcripts does decrease over time, with blood-specific transcripts detected for up to 12 months. This study aims to explore the use of total RNA degradation in bloodstain TSD models.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the degraded nature and low abundance of nucleic acid species render forensic samples a genuine challenge for any MPS experiment, several studies showed promising results when analyzing these kind of samples [11,12]. Also whole transcriptome sequencing (RNA-Seq) was successfully applied to forensic samples [13][14][15].…”
Section: Introduction: Transcriptomics and Potential Forensic Utilitymentioning
confidence: 99%
“…About 90% of blood and fresh menstrual blood reads could be aligned to the human reference genome, in contrast to 26-88% of oral mucosa and 5.6-59% of vaginal section reads.Since the oral cavity as well as the genital region are microbiota-rich environments, this finding would be expected[91][92][93]. Besides, they detected and confirmed known body fluid specific mRNA markers in samples of varying ages and presumably in differing states of degradation.Weinbrecht et al used RNA-Seq to analyze and characterize the time dependent degradation of blood, saliva, semen and vaginal secretion[14]. Samples were collected from two donors per body fluid and aged at room temperature (protected from light) for up to 1 year.…”
mentioning
confidence: 99%